Kepemimpinan Guru Pendidikan Agama Kristen - Nasib Tua Lumban Gaol; Andrianus Nababan (Universitas Kristen Satya Wacana, 2019)
Christian religious teacher leadership contributes to improving the learning process quality in school and national education contexts. Ironically, Christian religious teachers are still lacking knowledge in leadership, and not applying adequate leadership in the learning process. Thus, this paper was aimed to describe some characteristics of Christian religious teacher leadership that should be implemented. Based on the result of reviewing, these were found some of Christian religious teacher leadership characteristics: (1) serving students with the heart; (2) acting fair according to the truth of God's word; (3) having optimistic to educate; (4) able to manage time well; (5) loving students; (6) making decision objectively and firmly. In an effort to develop the Christian religious teacher leadership, further research and studies are needed to conduct in order to build the Christian religious teacher leadership concept.